2014
DOI: 10.3389/fonc.2014.00145
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Oncolytic Virotherapy: Advanced Tactics in the War against Cancer

Abstract: Cancer is a traitorous archenemy that threatens our survival. Its ability to evade detection and adapt to various cancer therapies means that it is a moving target that becomes increasingly difficult to attack. Through technological advancements, we have developed sophisticated weapons to fight off tumor growth and invasion. However, if we are to stand a chance in this war against cancer, advanced tactics will be required to maximize the use of our available resources. Oncolytic viruses (OVs) are multi-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 165 publications
(158 reference statements)
2
55
1
Order By: Relevance
“…These simulation results assert that combining chemotherapy and virotherapy to treat cancer is more effective and a good alternative to either chemotherapy or virotherapy alone, which is in agreement with the latest experimental studies [3,6,8,12,23,24,43,45,49,61,62]. These studies have shown that the right combination of oncolytic viruses and chemotherapy agents resulted in enhanced therapeutic effects not attainable by either therapy alone.…”
Section: Combining Chemotherapy and Virotherapysupporting
confidence: 86%
See 2 more Smart Citations
“…These simulation results assert that combining chemotherapy and virotherapy to treat cancer is more effective and a good alternative to either chemotherapy or virotherapy alone, which is in agreement with the latest experimental studies [3,6,8,12,23,24,43,45,49,61,62]. These studies have shown that the right combination of oncolytic viruses and chemotherapy agents resulted in enhanced therapeutic effects not attainable by either therapy alone.…”
Section: Combining Chemotherapy and Virotherapysupporting
confidence: 86%
“…Numerous experimental studies have shown that, with the right combination of oncolytic viruses and standard cytotoxic chemotherapy agents, synergistic interactions occur resulting in enhanced therapeutic effects not attainable by either therapy alone [6,43,45,49]. Chemovirotherapy has been experimentally and clinically tested for the treatment of some cancers such as malignant gliomas [3,61], lymphoma [62], lung cancers [23], and metastatic breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OVs expressing enzymes, antigens and/or cytokines may have particular utility in combination with chemotherapy. Genes previously studied with OV and found to increase their efficacy via induction of cell death include TRAIL, FasL, Ki-67 and others [119,120]. Expressible cytokines under investigation include IL-2, I IL-4, IL-18, IL-24, TNF-α and GM-CSF [119].…”
Section: Combination Therapy: Oncolytic Viruses and Chemotherapymentioning
confidence: 99%
“…Genes previously studied with OV and found to increase their efficacy via induction of cell death include TRAIL, FasL, Ki-67 and others [119,120]. Expressible cytokines under investigation include IL-2, I IL-4, IL-18, IL-24, TNF-α and GM-CSF [119]. IL-12 is of particular interest because it promotes the cytotoxic activity of NK cells and CD8+ T lymphocytes [121].…”
Section: Combination Therapy: Oncolytic Viruses and Chemotherapymentioning
confidence: 99%